Penerapan Model Discovery Learning pada Pembelajaran Garis Singgung Lingkaran untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa - Ahmad Febrian Rusdiansyah; Sripatmi Sripatmi; Yunita Septriana Anwar; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
The background of this research is the low activity and achievement of students' mathematics learning, one of which is due to the selection of learning models that are less varied. The activities of students are only limited to listening, taking notes, then doing practice questions. Discovery Learning is a learning model that directs students to be able to find concepts through the learning process they do which is expected to increase the activities and learning achievements of students. This type of research is a classroom action research (PTK) which is carried out in two cycles and each cycle contains the stages of action planning, action implementation, observation, and evaluation, as well as a reflection stage. The results showed that there was an increase in the activity and learning achievement of students where the learning activities of students in the first cycle with an average score of 10.51 were categorized as high, while in the second cycle with an average score of 13.67, they were categorized as very high. The average score of the learning evaluation results of students has increased in each cycle, namely in the first cycle the average score of the learning evaluation results was 72.65 with a percentage of 62.07% completeness and in the second cycle the average score of the learning evaluation results was 79.24 with a percentage of completeness of 86.21%. Based on the achievements obtained, it can be concluded that the Discovery learning model can increase the activity and learning achievement of students in learning tangents to circles.